Haptics Application in Dentistry: Is the Time Poised Yet? - Srinivas Sulugodu Ramachandra; B. G Boumya (Wolters Kluwer Medknow Publications, 2011)
The essence of dental education is not only to impart knowledge but also to equip an aspiring clinician with all the para-phernalia to face most clinical situations if not all. What be-comes important here is the requirement that a student be not only observant but also have a precise idea of what a lesion or a surface should feel like under an instrument. No matter how far we have come in terms of pathogenesis and treatment of diseases of the oral cavity, there is still no one good way to teach a student about the tactile sense, be it while de-tecting calculus/caries or placing the incisions or detecting the smoothness of a restoration. Most often than not students learn these by a trial and error method. A not-so-recent development called Haptics may well be the answer to this predicament, at least in the near future. The concept which is extensively in use and indis-pensable in other fields like aviation, telecommunication etc is now making inroads into dentistry. It is essentially software which brings in the idea of giving the feedback response to applied force, be it simple exploration of caries or the fine pressure applied in placing an incision or an array of other areas/situations in dentistry where fine tactile sense becomes a prerequisite for intelligent diagnoses or cutting edge treatment procedures. The following write-up is an attempt to throw light on this new technology and the impact it may have on pre-clinical teaching in dentistry. The advantages, disadvantages be-tween manikin based dental simulators and haptics based dental simulators are also pre-sented.